The story of Dombauyl from the Kiyat tribe (experience in interpreting the myth) - Zh. O. Artykbaev (Nomadic Civilization: Historical Research, 2021)
Oral sources are the most important source of study of the history of the Kazakh people and those that preceded them and other peoples of the Great Steppe Belt. Oral sources include epic poems, historical legends and legends, rhapsody, proverbs and sayings, other genres of oral folklore. They provide extensive information about the history of Kazakh and other steppe peoples, contain assessments of a certain event, their participants. The article attempts to analyze and interpret the myth-historical texts of the oral tradition of Kazakhs and other peoples of Central Asia, where the central ﬁgure is Dombauyl-mergen.